Pelatihan Pemanfaatan Google Form untuk Penyusunan Soal Ujian Interaktif bagi Guru di Smp Bahrul Ulum Kota Bontang - Lapu Tombi Layuk; Zaini Zaini; Abd. Rahim; Irfani Zuhrufillah (Universitas Perjuangan Tasikmalaya, 2026)
The development of digital technology requires teachers to adapt and integrate technology into the learning process. Coordination between the community service team and partners revealed that teachers still face difficulties in optimizing Google Form features, particularly in creating interactive questions. This community service activity aims to enhance teachers’ competence in utilizing Google Form as a digital assessment tool to support learning efficiency and effectiveness. The implementation methods include coordination and collaboration with partners, interactive training sessions, and direct mentoring for participants. The success of the activity was evaluated using a satisfaction questionnaire with a Likert scale to assess the implementation, material relevance, instructor competence, and the overall impact of the training. The results of the community service activity show that teachers successfully created interactive questions by optimizing Google Form features. Partner satisfaction with the training was very high, exceeding 93% across four aspects: activity implementation, material relevance, instructor competence, and training impact. During the training, teachers gained digital assessment skills and knowledge about educational transformation. As a follow-up, a communication group was established to ensure the sustainability of digital competency development.